Plantation milenial generation digital leadership and Its contribution in increasing individual performance at PTPN IV - R. Turino Januar Budyanto; Yusniar Lubis; Ahmad Rafiki (Jurnal Mantik, 2023)
This study aims to analyze the effect of digital leadership on performance, analyze the effect of digital leadership on talent management and analyze the effect of digital leadership on performance with talent management as an intervening variable at PTPN IV, one of the largest state-owned plantation companies in Indonesia. The population of this study is all millennial employees at the BOM (Board of Management) position level minus 1 to minus 3, a total of 400 people. The data collection method used was a questionnaire with a sample of 221 people. Data analysis technique using PLS-SEM. The results of the study show that digital leadership directly has a positive and significant effect on individual work, talent management has a positive and significant effect on individual work, digital leadership has a positive and insignificant effect on employee performance. Indirectly, job satisfaction does not mediate the relationship between motivational variables and employee performance variables. The results of this research are expected to be a reference for companies as material for consideration and input regarding the extent to which digital leadership and talent management influence employee performance. It is hoped that this research can provide ideas for companies in determining policies, especially in human resource management strategies.